(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Whole world has seen the havoc created by Coronavirus disease (COVID-19), which is an infectious disease. ’CO’ stands for corona, ’VI’ for virus, and ’D’ for disease. Formerly, this disease was referred to as ’2019 novel coronavirus’ or ’2019-nCoV.’ The COVID-19 virus is a new virus linked to the same family of viruses as Severe Acute Respiratory Syndrome (SARS) and some types of common cold. The recovery rate for someone suffering from COVID-19 varies from 92%-97% around the world, which is probably not a cause of concern. More concerning is that older people, and those with underlying medical problems like cardiovascular disease, diabetes, chronic respiratory disease, and cancer are more likely to develop serious illness and even can lead to death. The major concerns for the governments around the world was to control the transmission of this disease. The world which was known to be interconnected suddenly started closing borders. Even the states within countries sealed their borders. Flights were disrupted. Hospitality industry suffered a great financial loss. According to The World Travel and Tourism Council (WTTC), tourism generated 240 bn or 9.2% of India’s GDP in 2018 and supported 42.67 mn jobs which is 8.1% of its total employment. The industry saw major job loss and contraction in its revenues. This was the biggest motivator to carry out this research. Challenge is to come up with best possible routes during Covid-19 times and this could be extended to any such pandemic we might encounter in future as well. We propose two standard approaches to calculate risk for the travel locations in this paper. The two approaches are: • Approach 1: Risk calculation based on main travel locations’ active cases, and • Approach 2: Risk calculation based on main travel locations and locations’ immediate neighbours In our research, Covid-19 dataset for India has been used and that has been downloaded from the government official website. Though the proposed solution can be applied in any country/area map, our experiment is mainly focus India as we have used India’s Covid-19 dataset. Our proposed algorithms connects with Google Maps and suggest risk associated with all the possible routes between source and destination for the traveller and traveller can choose the low risk route for this travel. We want to make sure the world remains connected and no other such pandemic should stop the movement of goods or people.